THE EFFECT OF VARYING TYPES DRILL TECHNIQUE ON ENGLISH PRONUNCIATION OF GRADE-8 STUDENTS OF SPMN 23 MAKASSAR - Fadli Ardima (Publikasi dan UKI Press UKI Toraja., 2020)
This study aims to know the effect of drill technique on student’s English pronunciation. The study employed Quasi-experimental design. The population consists of 39 students and the sample were 20 students taken from the grade-8 students of SMPN 23 Makassar. The data was collected by administering filling the blank oral test with consisting of 30 words/sentences. The result of this research shows that of T-test is higher than T- table (4.634 ? 2.093). The result indicates that the alternative hypothesis(H1) is accepted and of course the null hypothesis (H?) is rejected, it shows that using drill technique has affected on students’ English pronunciation used the reading text as teaching tools of oral test in the classroom.